Localized salt‐dependent aquagenic urticaria: a subtype of aquagenic urticaria?. (30th July 2013) - Gallo, R.; Gonçalo, M.; Cinotti, E.; Cecchi, F.; Parodi, A.
Summary Aquagenic urticaria is a rare form of inducible urticaria characterized by wealing at the site of contact of the skin with water, regardless of its temperature, within minutes of exposure. We describe six young women who reported urticarial rashes, triggered mostly by sea bathing, characteristically localized on the inferior facial contours and neck. In four of the six patients, this was the only localization. All six reacted with erythema and wealing to challenge tests with hypertonic saline (3.5% NaCl) applied to the submandibular area and/or neck. Two patients reacted also to tap water or to normal saline, but less intensely. Challenge tests with different hypertonic water solutions, performed in one patient, showed that both salinity and hypertonicity may be pathogenically relevant. Response to antihistamines was poor in three patients. Our experience suggests the existence of a distinct salt‐dependent subtype of aquagenic urticaria (SDAU) that affects young women, with a characteristic localization on the inferior facial contours and neck. SDAU is possibly under‐recognized and under‐reported.